Epidemiological characteristics of trauma patients - Pekdemir, M.; Cete, Y.; Eray, O.; Atilla, R.; Cevik, A.A.; Topuzoglu, A. (My University, 2000)
We have evaluated retrospectively adult trauma patients admitted to the Dokuz Eylul University Hospital Emergency Department (ED) between 1.1.1997-30.6.1997 by the aim of contributing epidemiological data about trauma related injuries of Turkey. Among the 1063 study patients, 626 patients were male, 437 patients were female and mean age of the patients was 40.6 +/- 18. The most common causes of injury was fall. The revised trauma score lesser than 12 was 75 patients. It has been determined that 90.8% of the patients were brought to ED by the vehicles other than the ambulance. Among all patients, 872 patients (82%) were discharged from ED, 118 patients (11.1%) were admitted, 73 patients (6.9%) were referred to another hospitals and 13 patients (1.2%) were died. We have determined the significantly increased hospital admission rate in the subgroups of the penetrating trauma patients, patients older than 65 years old (p = 0.001 and 0.003, respectively) and the significantly increased operative intervention and death in penetrating trauma patients (p = 0.000 and 0.009, respectively).
Travma hastalarinin epidemiyolojik özelliklerinin araştirilmasi.
Keywords: Accidental Falls; Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Emergency Treatment; Female; Humans; Male; Middle Aged; Patient Admission; Retrospective Studies; Risk Factors; Transportation of Patients; Trauma Severity Indices; Turkey; Wounds and Injuries; adolescent; adult; age; aged; article; emergency treatment; falling; female; hospital admission; human; injury; injury scale; male; middle aged; pathology; patient transport; retrospective study; risk factor; statistics; Turkey (republic)